2022
DOI: 10.23736/s0022-4707.21.13144-5
|View full text |Cite
|
Sign up to set email alerts
|

Can small-sided games assess the training-induced aerobic adaptations in elite football players?

Abstract: BACKGROUND: To investigate whether or not SSGs could be used to evaluate the aerobic fitness status and the longitudinal training-induced adaptations in football players. Additionally, the capacity of SSGs to recreate the official match demands was investigated.METHODS: Twenty-five elite football players were monitored. Total distance (TD), high-speed running, very high-speed running, sprint and accelerations plus decelerations distance were measured during 20 SSGs formats and 25 official-matches; in SSGs, ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These similar physical demands before and after the inactivity period may be due to the following: (a) a short period of detraining, not originated changes in physical fitness, however, as in previous studies, 2,35 a lower performance in the RSA after detraining has been detected; (b) the variability of physical demands in small games 41 and (c) SSGs are not considered sensitive for assessing physical fitness level. 39,46 In conclusion, the results showed that the effects of 2-week in-season break inactivity are dependent on the type of capacity assessed, as significant impairment in CMJ, RSA Sdec and RSA mean performance was observed, without changes in RSA best or locomotor performance in SSGs. However, contrary to previous studies showing that a short period of time without training can cause a taper effect and increase performance, only 2-week in-season break inactivity decreases RSA performance, a determining capacity for performance in female soccer players.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These similar physical demands before and after the inactivity period may be due to the following: (a) a short period of detraining, not originated changes in physical fitness, however, as in previous studies, 2,35 a lower performance in the RSA after detraining has been detected; (b) the variability of physical demands in small games 41 and (c) SSGs are not considered sensitive for assessing physical fitness level. 39,46 In conclusion, the results showed that the effects of 2-week in-season break inactivity are dependent on the type of capacity assessed, as significant impairment in CMJ, RSA Sdec and RSA mean performance was observed, without changes in RSA best or locomotor performance in SSGs. However, contrary to previous studies showing that a short period of time without training can cause a taper effect and increase performance, only 2-week in-season break inactivity decreases RSA performance, a determining capacity for performance in female soccer players.…”
Section: Discussionmentioning
confidence: 78%
“…These similar physical demands before and after the inactivity period may be due to the following: (a) a short period of detraining, not originated changes in physical fitness, however, as in previous studies, 2,35 a lower performance in the RSA after detraining has been detected; (b) the variability of physical demands in small games 41 and (c) SSGs are not considered sensitive for assessing physical fitness level. 39,46…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors concluded that HIIT is not superior to constant intensity endurance training (CIET) in improving aerobic or anaerobic parameters in adolescents. The research regarding the importance of SSG on the optimization of sports performance in sports games in general [54][55][56][57][58], and in football in particular, is numerous, as is made evident by their positive impact on psychological, physical, tactical and technical skills in the sports training process and in competitive games, for all age groups [59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%